Addressing ethical challenges in HIV prevention research with people who inject drugs. Issue 3 (25th April 2016) - Dawson, Liza; Strathdee, Steffanie A; London, Alex John; Lancaster, Kathryn E; Klitzman, Robert; Hoffman, Irving; Rose, Scott; Sugarman, Jeremy
Abstract : Despite recent advances in HIV prevention and treatment, high HIV incidence persists among people who inject drugs (PWID). Difficult legal and political environments and lack of services for PWID likely contribute to high HIV incidence. Some advocates question whether any HIV prevention research is ethically justified in settings where healthcare system fails to provide basic services to PWID and where implementation of research findings is fraught with political barriers. Ethical challenges in research with PWID include concern about whether research evidence will be translated into practice; concerns that research might exacerbate background risks; and ethical challenges regarding the standard of HIV prevention in research. While these questions arise in other research settings, for research with PWID, these questions are especially controversial. This paper analyses four ethical questions in determining whether research could be ethically acceptable: (1) Can researchers ensure that research does not add to the burden of social harms and poor health experienced by PWID? (2) Should research be conducted in settings where it is uncertain whether research findings will be translated into practice? (3) When best practices in prevention and care are not locally available, what standard of care and prevention is ethically appropriate? (4) Does the conduct of research in settings with oppressive policies constitute complicity? We outline specific criteria to address these four ethical challenges. We also urge researchers to join the call to action for policy change to provide proven safe and effective HIV prevention and harm reduction interventions for PWID around the world.